2015
DOI: 10.1097/ta.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

Dead or alive? New confirmatory test using quantitative analysis of computed tomographic angiography

Abstract: Diagnostic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
3
0
2
Order By: Relevance
“…13 Because tests of cerebral perfusion such as CTA are actually tests of cerebral circulatory arrest, these are the most appropriate tests to use when attempting to clarify an ambiguous diagnosis of BD, as they tend to have the smallest falsepositive rates. 2,14,18 Our data support these claims, as CTA maintained a specificity of 100% and a sensitivity of 75% in our test population. Test sensitivity in this context refers to the number of patients who meet the gold-standard criteria for BD but have CTA findings that do not meet the stated criteria for BD (opacification above the level of the petrous ICAs, intradural VAs, or ICVs).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…13 Because tests of cerebral perfusion such as CTA are actually tests of cerebral circulatory arrest, these are the most appropriate tests to use when attempting to clarify an ambiguous diagnosis of BD, as they tend to have the smallest falsepositive rates. 2,14,18 Our data support these claims, as CTA maintained a specificity of 100% and a sensitivity of 75% in our test population. Test sensitivity in this context refers to the number of patients who meet the gold-standard criteria for BD but have CTA findings that do not meet the stated criteria for BD (opacification above the level of the petrous ICAs, intradural VAs, or ICVs).…”
Section: Discussionsupporting
confidence: 84%
“…9,15 Furthermore, the statistical performance of CTA reported in the literature is similar to that of EEG and TCD, 2 AAN-approved ancillary tests. 2,9,14,15,18 Numerous radiological criteria exist for interpreting CTA results in patients suspected of being brain dead, with widely varying sensitivities resulting from how many and which vessels are included in a given criteria. In 2009, Frampas et al 6 compared the standard French 7-vessel criteria (nonopacification of pericallosal and cortical segments of the MCAs, ICVs, and great cerebral vein) with a 4-vessel criteria (nonopacification of cortical segments of MCAs and ICVs) and found that, by using the 4-vessel criteria, sensitivity was improved from 62.8% to 85.7% while maintaining a specificity of 100%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suarez-Kelly et al. [ 8 ] hatten als Studienergebnis mitgeteilt, dass ein intraarterieller Schwellenwert von 80 Hounsfield Units (HU) für die Unterscheidung von erhaltener Hirndurchblutung und sistierender zerebraler Zirkulation (Stasis filling) geeignet sei. Ein in dieser Größenordnung gelegener Schwellenwert war auch von Welschehold et al.…”
Section: Noch Erforderliche Bestätigungenunclassified